Stem cell self-renewal and recovery of intestinal epithelial barrier dysfunction associated with alcohol abuse. Issue 2 (2019) - , Ichiaki Ito; , Sam Jacob; , Sumihiro Suzuki; Kobayashi, Makiko; Suzuki, Fujio
No abstract available